Application of Problem Based Learning (PBL) Model to Improve Higher Order Thinking Skills (HOTS) - Firda, Firda; Hadiwijaya, Rizki; Nugraha, Fajar (Universitas Sebelas Maret, 2021)
This research was motivated by the low level of high-order thinking skills of students on the material of human respiratory organs at SDN Cibungbun, Tasikmalaya Regency, of 27 students only 9 students who completed getting high-order thinking skills scores, with very high criteria of 5 people, high criteria of 2 people. and the criteria are enough for 2 people. Based on this, the researcher applied the Problem Based Learning (PBL) learning model. This study used a Classroom Action Research (CAR) model. Data collection obtained through tests, observation, and documentation. The results obtained: 1) The application of the Problem Based Learning model increases Higher Order Thinking Skills. The results of the value of teacher activity in the first cycle increased from 78% in the good category, and in the second cycle to 93% in the very good category. 2) Increasing the results of students' higher order thinking skills. The results of students' high-order thinking skills in pre-cycle 63, then in cycle I with an average value of 72, while in cycle II with an average value of 83. The results of research on teacher activity, student activity, and results of Higher Order Thinking Skills have changed towards a better direction, it can be concluded that the use of the PBL learning model can increase Higher Order Thinking Skills in class V SDN Cibungbun, Rajapolah District.